Implementing Pediatric Integrative Medicine in Practice - McClafferty, Hilary (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue provides an overview of pediatric integrative medicine, an emerging field that blends conventional and evidence based complementary therapies with an emphasis on preventive health and wellbeing.